(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article is written on the materials of an international ethnographic expedition to the Issyk-Kul region from September 14 to 24, 2021. The author’s research focuses on the problems of the historical settlement of the titular nation and the newcomer population.